2022
DOI: 10.31234/osf.io/bfj9w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mind over body: Interfering with the inner voice is detrimental to endurance performance

Abstract: In two preregistered experiments, we investigated whether people were less able to push themselves physically when distracted from using their internal language. In both experiments, participants performed 12 cycling trials (Experiment 1: N = 49; Experiment 2: N = 50), each lasting one minute where participants were required to cycle as fast as possible while engaging in either a visuospatial task, a verbal task or with no interference. Participants performed worse in the verbal interference condition compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…A study (Nedergaard, et al, 2021) found that the content of self-talk, as measured with a version of the Automatic Self-Talk Questionnaire for Sports (Zourbanos, et al, 2009), was predictive of best running time in long-distance running. We also found that interfering with self-talk using verbal interference (Nedergaard, et al, 2022b), causes participants to cycle slower on an exercise bike compared to a non-verbal interference task (Nedergaard, et al, 2022a). This suggests that spontaneous and/or goal directed self-talk is a causal factor in endurance sports.…”
Section: Frequency Of Self-talk In Endurance Sportmentioning
confidence: 62%
“…A study (Nedergaard, et al, 2021) found that the content of self-talk, as measured with a version of the Automatic Self-Talk Questionnaire for Sports (Zourbanos, et al, 2009), was predictive of best running time in long-distance running. We also found that interfering with self-talk using verbal interference (Nedergaard, et al, 2022b), causes participants to cycle slower on an exercise bike compared to a non-verbal interference task (Nedergaard, et al, 2022a). This suggests that spontaneous and/or goal directed self-talk is a causal factor in endurance sports.…”
Section: Frequency Of Self-talk In Endurance Sportmentioning
confidence: 62%
“…It seems to be the case that task-relevant, focused self-talk is recruited under circumstances that are highly demanding, either because the athlete is learning a new sport (Zourbanos et al, 2013), competing against others (Dickens et al, 2018; Thibodeaux & Winsler, 2018; Van Raalte et al, 2000) or under high intensity (Aitchison et al, 2013; Nedergaard et al, 2021). In the first study to test self-talk and physical performance with a dual-task interference paradigm (Nedergaard, Wallentin, & Lupyan, 2022), Nedergaard, Christensen, and Wallentin (2022) found that participants who cycled on an exercise bike while engaged in simultaneous verbal interference were slower than when they were cycling without interference. In dual-task paradigms such as this, a specific negative effect of verbal interference is taken to mean that participants under normal circumstances benefit (in this case in the form of better cycling performance) from being able to talk to themselves (see Nedergaard, Christensen, & Wallentin, 2022, for a comprehensive review of the verbal interference literature).…”
Section: Inner Speech and Behavioral Controlmentioning
confidence: 99%
“…In the first study to test self-talk and physical performance with a dual-task interference paradigm (Nedergaard, Wallentin, & Lupyan, 2022), Nedergaard, Christensen, and Wallentin (2022) found that participants who cycled on an exercise bike while engaged in simultaneous verbal interference were slower than when they were cycling without interference. In dual-task paradigms such as this, a specific negative effect of verbal interference is taken to mean that participants under normal circumstances benefit (in this case in the form of better cycling performance) from being able to talk to themselves (see Nedergaard, Christensen, & Wallentin, 2022, for a comprehensive review of the verbal interference literature).…”
Section: Inner Speech and Behavioral Controlmentioning
confidence: 99%